2020
DOI: 10.1111/den.13705
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of laparoscopic endoscopic cooperative surgery for non‐ampullary superficial duodenal neoplasms: Single‐arm confirmatory trial

Abstract: Objective Laparoscopic endoscopic cooperative surgery for duodenal tumors (D‐LECS) has been developed to prevent duodenal leakage by reinforcing the endoscopic submucosal dissection site. However, there has been no prospective trial showing the feasibility of D‐LECS. Herein, we conducted a single‐arm confirmatory trial to evaluate the safety of D‐LECS for non‐ampullary superficial duodenal neoplasms. Methods This prospective single‐center single‐arm confirmatory trial analyzed patients with non‐ampullary super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 24 publications
(59 reference statements)
0
17
0
Order By: Relevance
“…Although LECS was developed for gastric submucosal tumors [ 27 ], it has also been adapted for duodenal tumors (D-LECS) [ 28 , 29 ]. D-LECS can be divided into two types depending on whether performing perforation during endoscopic treatment: full-thickness resection (with perforation: D-LECS with FTR) or ESD with reinforcement using a laparoscopic approach (without perforation: D-LECS with ESD).…”
Section: Review Of Endoscopic Treatment For Snadetsmentioning
confidence: 99%
“…Although LECS was developed for gastric submucosal tumors [ 27 ], it has also been adapted for duodenal tumors (D-LECS) [ 28 , 29 ]. D-LECS can be divided into two types depending on whether performing perforation during endoscopic treatment: full-thickness resection (with perforation: D-LECS with FTR) or ESD with reinforcement using a laparoscopic approach (without perforation: D-LECS with ESD).…”
Section: Review Of Endoscopic Treatment For Snadetsmentioning
confidence: 99%
“…Until now, few studies have compared LECS and laparoscopy-only groups for duodenal tumors, and most were single-arm confirmatory trials, case reports, or offered only technical tips regarding LECS [ 9 10 12 13 ]. As a comparative study, Ojima et al [ 11 ] concluded that LECS was an ideal alternative to endoscopic resection for low-risk duodenal tumors in terms of complication and curative resection rates.…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic resection may adequately treat SNADTs. However, difficulty in determining tumor location may lead to unnecessary laparoscopic duodenal resection [ 10 ]. Laparoscopic endoscopic cooperative surgery (LECS), which exploits the advantages and minimizes the disadvantages of endoscopic and laparoscopic treatments, may be appropriate [ 9 10 11 12 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the much higher risk of AEs with ESD, several endoscopic methods, such as line-assisted closure 8 , ENBPD 9 and over-the-scope clip closure 10 11 have been introduced for the prevention of AEs. More recently, Kanaji et al reported the safety and feasibility of laparoscopic cooperative surgery for duodenal tumors (D-LECS) 29 . In the present study, AEs occurred in four cases treated by ESD.…”
Section: Discussionmentioning
confidence: 99%